Pemanfaatan serbuk kayu bulian (eusideroxylon zwagery t et b) sebagai antimakan terhadap ulat jengkal, chrysodeixis chalcites - Johari, Asni (Universitas Jambi, 2010)
There is a growing concern to use environmentally friendly pesticides including the use of plant-based pesticides. Given that bio pesticides are degraded easily, exploration and scanning to obtain new bio insecticides are continued to be practiced. One of the potential bio insecticides is bulian (Euderoxylon zwagerii). The bulian is a species of hardwood commonly used as construction material by the people of Jambi due to its resistance to termite and mold. The earlier research indicated that the sawdust of bulian is potential to treat Spodoptera litura F., an important crop pest. The purpose of this research is to develop active agents extracted from bulian sawdust to control pest crop especially C. Chalcites. The treatment include the application of bulian extract with concentration of 0,01%, 0,05%, 0,1%, 0,5%, and 1%. The smallest concentration of active extract with the strongest anti-feeding activity will be used as a reference for the following field studies of C. Chalcites. The results showed that, the higher the concentration of n-hexane extract is given, the higher the antifeedant activity of C. Chalcites. The smallest concentration that showed very strong anti-feeding of C. Chalcites is 0.5%